The mystery at Number Seven, Rue Petite - Shire, Ellen (New York : Random House, 1978)
Isabelle and Jean-Pierre are curious about the locked room in the house of their employer, an antique dealer.
School Library Journal
3.7
K-3
Keywords: Mystery and detective stories; Paris (France) -- Fiction; Mystery and detective stories; Paris (France) -- Fiction